A chiral spiroborate anion from diphenyl-l-tartramide [Bl-Tar(NHPh)22]− applied to some challenging resolutions. Issue 33 (31st July 2018) - Wong, Lawrence W.-Y.; Tam, Gemma S.-S.; Chen, Xiaoyan; So, Frederick T.-K.; Soecipto, Aristyo; Sheong, Fu Kit; Sung, Herman H.-Y.; Lin, Zhenyang; Williams, Ian D.
Abstract : A chiral spiroborate anion [Bl -Tar(NHPh)2 2 ] − is effective in challenging high yield, 1-pot resolutions, as for the S-2-phenylpropylammonium salt shown. Abstract : The chiral spiroborate anion [Bl -Tar(NHPh)2 2 ] − has been prepared as simple salts K, NH4, Na in high yield and purity. Its structural features have been examined by single crystal XRD and DFT calculations and indicate that conformational arrangements are dominated by intramolecular NH—O{C inter-amide hydrogen bonds. These confer predictable shape, as well as a clear binding site for ion-pair formation. The potential of this anion for resolution by diastereomeric salt formation was then tested using five challenging racemic amines of type NH2 CHR1 R2 with high shape similarity between their enantiomers. Organo-ammonium salts from these were made directly from a simple 1-pot reaction from racemic amine, boric acid and 2 eq. N, N ′-diphenyl-l -tartramide in MeOH. The products are single phase crystalline solids with moderate to excellent enantioexcesses up to 95% ee. They show conserved NH3 R + binding and layered packing arrangements, all with short 5.5 Å axes. Based on chiral HPLC the initial [Bl -Tar(NHPh)2 2 ] salt from rac -phenylglycinol has [S-NH3 CH(CH2 OH)Ph] + with 95% ee and the salt from rac -1-phenylpropylamine is also well resolved (>91% ee) in a single step. Three disorder modes that limit resolution in the other salts were identified at the cation site – H/R1 site exchange, R1 /R2 site exchange or C–H re-pyramidalization. Extension to a family of such aryltartramide anions may allow crystal engineering of the cation binding pockets to overcome the disorder inherent to such resolutions.